Development of Model of Water Conservation through PAIC Process - Udonboon, Chalermsak; Thiengkamol, Nongnapas; Thiengkamol, Chatchai (Richtmann Publishing, 2012)
The objective of this research was to develop a model of water conservation for secondary school student. Theintegrative method research was done with participatory action research with Participatory Appreciate-Influence-Controltechnique (PAIC). Populations were upper secondary school students of academic year 2012 of Kalasin Province. Thequestionnaire and evaluation forms were be used as tool for data collection and the sample was selected by purposive samplingtechnique. PAIC was implemented with the integration of SWOT analysis and brain storming during the training process. The 53upper secondary school students were selected by purposive sampling technique from Kalasin Pittayasan School, AmphurMuang, Kalasin Province for training with PAIC. One -Way-ANOVA and t-test were used for data analysis.The research resultsillustrated that before and after PAIC process implemented, the mean scores of posttest of training achievement The researchresults revealed that before and after PAIC training process implemented, the mean scores of posttest of training achievementon characteristics of Environmental Education Trainer (EET), inspiration of public consciousness, environmental conservationbehavior, water conservation, and training achievement were higher than pretest with statistical significance (p< .01, p< .01, p<.01, p< .01, and p< .01). Three Dimensional Evaluations were employed for determination the perceptions of 53 uppersecondary school students in three aspects evaluation covering Self-evaluation, Friend-evaluation, and Facilitator-evaluation byusing One-way ANOVA in order to investigate the participation of upper secondary school students showed that there were nodifference of mean scores about participation in training process through brain storming with statistical significance (p>.05).